EVALUASI OUTPUT INOVASI PELAYANAN PUBLIK BRT TRANS SEMARANG MENGGUNAKAN PEMBAYARAN GOPAY - Astri Kurniawati; Hendra Try Ardianto (Journal of Politic and Government Studies, 2020)
The study evaluated the implementation of the BRT Trans Semarangpublic service innovation using Gopay payments accompanied by the viewpointof the community as service users. The innovation is supported by the product ofa private company namely PT Dompet Anak Bangsa with the Semarang CityGovernment who wants the people of Semarang to become accustomed to usingcashless in supporting the principle of Semarang Smart City.The author uses a mixed method by giving questions to research subjectsby interviewing technical implementers and Semarang users, Trans SemarangBRT staff stakeholders and collecting data in the field and documentation ofresearch objects. Seeing the innovation of BRT Trans Semarang services usingRoger's theory in (Suwarno, 2008) relative advantages, compatibility,complexity, possibilities to try, or easily observed.Whereas in evaluating the output of public service innovation to users ofthe Trans Semarang BRT service using criteria according to William Dunn in(Fitriana, 2019, p. 19) namely effectiveness, adequacy, equity, responsivenessand accuracy, the policies that have been carried out by looking at how muchimpact on the community as a service user.Public service innovations carried out by the Trans Semarang UPTDPublic Service Agency using Gopay are good enough, four indicators out of thesix used indicators have been met which are effectiveness, efficiency, adequacy,leveling and other indicators that have not been met are responsiveness andaccuracy.Keywords: Public service innovation, evaluation of public services, BRT TransSemarang